2020
DOI: 10.1002/ehf2.12751
|View full text |Cite
|
Sign up to set email alerts
|

Watershed phenomena during extracorporeal life support and their clinical impact: a systematic in vitro investigation

Abstract: Aims Extracorporeal life support (ECLS) during acute cardiac failure restores haemodynamic stability and provides life-saving cardiopulmonary support. Unfortunately, all common cannulation strategies and remaining pulmonary blood flow increase left-ventricular afterload and may favour pulmonary congestion. The resulting disturbed pulmonary gas exchange and a residual left-ventricular action can contribute to an inhomogeneous distribution of oxygenated blood into end organs. These complex flow interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The decreased preload and increased afterload may reduce the patient's own cardiac output. In patients with VA-ECMO, head and brain perfusions are determined according to the balance between VA-ECMO pump flow and the patient's own cardiac output (34,35). Further studies are required to investigate whether sublingual microcirculation is correlated with cerebral blood flow in patients with VA-ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased preload and increased afterload may reduce the patient's own cardiac output. In patients with VA-ECMO, head and brain perfusions are determined according to the balance between VA-ECMO pump flow and the patient's own cardiac output (34,35). Further studies are required to investigate whether sublingual microcirculation is correlated with cerebral blood flow in patients with VA-ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…In this cannulation approach, ECMO provides continuous retrograde perfusion into the distal aorta which then collides with pulsatile antegrade perfusion from the heart to create a dynamic watershed region with mixing of the colliding flows 17,18 . The complex hybrid circulation generated by dual perfusion from the ECMO circuit and the heart, termed here as the ECMO:failing heart circulation 18 , differs significantly from physiologic ventriculo-vascular interactions as the left ventricle ejects against continuous retrograde filling of the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the LVEDV did not differ between the experimental groups, implying that the ECMO-induced watershed has not increased the afterload or moved towards the heart. Moreover, experiments with an in-vitro mock circulation loop demonstrated that an increased ECMO flow was unable to shift the watershed towards the aortic arch [ 30 ]. In summary, this study underlines the importance to avoid apnea during awake V-A ECMO with femoral cannulation in order to lower the risk for pulmonary and coronary hypoxia.…”
Section: Discussionmentioning
confidence: 99%